1990
DOI: 10.1002/dvg.1020110515
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory gene interactions controlling discoidin lectin expression in Dictyostelium discoideum

Abstract: Genetic studies have revealed a network of three unlinked regulatory genes that control the developmental expression of the family of endogenous lectins in Dictyosteliurn discoideurn.Mutations in the disA and dis5 loci have a null phenotype and do not express the discoidin I or I I lectins. The third mutation, drsA, is a second-site suppressor of the dis5 mutation, which restores expression of all lectin species. Cells carrying this mutation express the discoidin lectins during growth, which is in contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…both growing and developing cells (1,4). This is in contrast to wild-type cells which first begin to accumulate discoidin during the aggregation phase of development.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…both growing and developing cells (1,4). This is in contrast to wild-type cells which first begin to accumulate discoidin during the aggregation phase of development.…”
Section: Resultsmentioning
confidence: 78%
“…In contrast, cAMP has been shown to be a negative regulator of discoidin gene transcription (34), since cAMP accumulation during development results in cessation of transcription of these genes. Recently, we have shown that cAMP, as well as folic acid, also negatively regulates discoidin lectin expression during growth of axenic cells (4 (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, gdt1 may be in a parallel, interacting pathway. The idea that discoidin expression is controlled by a network of pathways was already proposed by Alexander et al (1986Alexander et al ( , 1990. It should be noted that the double mutant also shows that G␣2-mediated signaling apparently splits into two branches: although the GDT (i.e.…”
Section: Discussionmentioning
confidence: 80%